Correlation between the Warburg effect and progression of triple-negative breast cancer - Liu, Shaojun; Li, Yuxuan; Yuan, Meng; Song, Qing; Liu, Min (Frontiers in Oncology, 2023)
Negative expression of the estrogen receptor, progesterone receptor, and human epidermal growth factor receptor-2 disqualifies triple-negative breast cancer (TNBC) as a candidate for hormonal therapy and Her-2-targeted therapy. Although targeted therapy and immunotherapy have been shown to attenuate the aggressiveness of TNBC partially, few patients have benefited from them. Chemotherapy is still the standard treatment for TNBC. However, chemoresistance hinders treatment progress over time, and chemotherapy toxicity aggravates the cancer burden on patients. Therefore, introducing more advantageous TNBC treatment options is a necessity. Metabolic reprogramming centered on glucose metabolism is considered a hallmark of tumors. It is described as tumor cells tend to convert glucose to lactate even under normoxic conditions, known as the Warburg effect. Its occurrence is attributed to the selective pressures caused by the harsh conditions of the microenvironment of pre-malignant lesions, similar to the Darwinian evolutionary process. Of note, the Warburg effect does not disappear with changes in the microenvironment after the formation of malignant tumor phenotypes. Instead, it forms a constitutive expression mediated by mutations or epigenetic modifications, providing a robust selective survival advantage for primary and metastatic lesions. Expanding evidence has demonstrated that the Warburg effect mediates multiple invasive behaviors in TNBC, including proliferation, metastasis, recurrence, immune escape, and multidrug resistance. Moreover, the Warburg effect-targeted therapy has been testified to be feasible in inhibiting TNBC progression. However, not all TNBCs are sensitive to glycolysis inhibitors because TNBC cells flexibly switch their metabolic patterns to cope with different survival pressures, namely metabolic plasticity. Metabolic plasticity sets a chasm between the Warburg effect-targeted therapies and the actual curative effect that needs to be constantly explored and attempted to bridge.